Group scheduling with deteriorating jobs and allotted resource under limited resource availability constraint. Issue 2 (1st February 2019) - Wang, Ji-Bo; Liang, Xi-Xi
ABSTRACT: This study considers a single machine group scheduling problem with deteriorating jobs and resource allocation (controllable processing times). The objective is to have the resource availability limited within a given range, and to minimize the maximum completion time ( i.e. the makespan). For two special cases, it is proved that the problem can be solved in polynomial time. For the general case, an heuristic algorithm and a branch-and-bound algorithm are proposed. Computational results show that the proposed heuristic algorithm is generally effective.